IMPLEMENTATION AND INSTRUMENTATION CHARACTERISTIC ANALYSIS OF A DIGITAL BODY TEMPERATURE MEASUREMENT SYSTEM USING A DS18B20 SENSOR - Rindra Angga Wibowo; Aril Yudatmo; Aulya Ghaitsha Faira; Nabilla Alya Septiani; Mukhamad Widodo (TESLA: Jurnal Teknik Elektro, 2026)
Temperature measurement is a critical parameter in various fields, particularly healthcare and industry, as it relates to environmental conditions and process stability. This study aims to design and analyze the characteristics of a digital temperature measurement system based on an Arduino Uno microcontroller, utilizing a DS18B20 sensor and an OLED display. The system is designed to acquire temperature data in real-time and display measurement results directly on the screen. Testing was conducted at several reference temperature points within the biological temperature range using a comparison method against a standard measuring instrument. The test results show that the system has an average accuracy of 99.87%, an average error of 0.045°C, and an average precision of 0.154°C. Linearity analysis indicates a good relationship between reference temperature and measured temperature with a sensitivity of 1.012°C/°C. Based on these characteristics, the system performs well within the biological temperature range, making it a potential candidate for use as a body temperature monitoring device. The suitability of use in healthcare applications must comply with medical temperature measurement standards such as ISO 80601-2-56 or ASTM E1112. Additionally, with a sensor measurement range of −55°C to 125°C, the system also has the potential for use in small-scale industrial applications such as monitoring incubator temperatures, storage rooms, and low-temperature drying processes. Abstrak Pengukuran suhu merupakan parameter penting dalam berbagai bidang, terutama kesehatan dan industri, karena berkaitan dengan kondisi lingkungan dan stabilitas proses. Penelitian ini bertujuan merancang dan menganalisis karakteristik instrumentasi sistem pengukuran suhu digital berbasis mikrokontroler Arduino Uno menggunakan sensor DS18B20 dan tampilan OLED. Sistem dirancang untuk melakukan akuisisi data suhu secara real-time dan menampilkan hasil pengukuran secara langsung pada layar. Pengujian dilakukan pada beberapa titik temperatur referensi dalam rentang suhu biologis dengan metode perbandingan terhadap alat ukur standar. Hasil pengujian menunjukkan sistem memiliki akurasi rata-rata sebesar 99,87%, error rata-rata 0,045°C, dan presisi rata-rata 0,154°C. Analisis linearitas menunjukkan hubungan yang baik antara suhu referensi dan suhu terukur dengan sensitivitas sebesar 1,012°C/°C. Berdasarkan karakteristik tersebut, sistem memiliki kinerja yang baik pada rentang suhu biologis sehingga berpotensi digunakan sebagai perangkat pemantauan suhu tubuh. Kelayakan penggunaan pada aplikasi kesehatan perlu mengacu pada standar alat ukur temperatur medis seperti ISO 80601-2-56 atau ASTM E1112. Selain itu, dengan rentang pengukuran sensor −55°C hingga 125°C, sistem juga berpotensi digunakan pada aplikasi industri berskala kecil seperti pemantauan suhu inkubator, ruang penyimpanan, dan proses pengeringan bersuhu rendah.